Carbohydrate supplementation does not improve a 10 km swim performance - Baldassarre, R.; Piacentini, M. F.; Patrizio, F.; Sachetti, M. (20th Annual Congress of the European College of Sport Science (ECSS), 24th-27th June 2015, Malmö -Sweden. Book of Abstracts, 2015)
Introduction For exercise lasting more than 2h, it is well established that carbohydrate (CHO) ingestion during exercise can improve exercise performance by preventing hypoglycemia, maintaining high rates of CHO oxidation and therefore increasing endurance capacity (Jeukendrup 2014). While most research focused on running and cycling, there is a lack of studies focusing on open water endurance swimming. Therefore, the aim of the present study was to evaluate the effects of the ingestion 60 g.h-1 of carbohydrates on a 10km swim performance. Moreover, the present study represents the first attempt to monitor glycemia continuously during an endurance swimming event. Methods Ten elite open-water swimmers (6 male and 4 female; 22±5yrs, 1.76±0.05m, 70.5±7kg) volunteered for the present study. In two difference occasions in a random order, they were asked to perform a 10km swim (20x500m) in a 25m indoor pool, ingesting every 2.5km either water (WAT) or a solution of water and 60 g/h of CHO. Every 1000m athletes had to rate their perceived exertion (RPE) on the 6-20 scale. Glycemia was monitored throughout the test with continuous glucose monitoring (CGM) (iPro 2, Medtronic). A two-way ANOVA was used to analyze the effect of trial on parameter time course (p<0.05). Results Performance was not different between the two trials (1:54:26±0:04:09 h:m:sec CHO; 1:54:27±0:04:26 h:m:sec WAT). RPE increased significantly throughout both trials, with no differences between CHO or WAT. No signs of hypoglycemia were found during the WAT trial. Glycemia increased the last 3km of the CHO trial (107.5±7.7; 113.0±7.0; 118.7±9.1 mg/dl) and was significantly higher compared to the same time points in the WAT trial (101.4±11.4; 104.3±12.5; 105.8±13.8 mg/dl). Discussion Open water events longer than 5-km may be considered glycogen depleting (Costill et al. 1988). However, supplementation with 60 g/h of CHO did not increase a simulated 10 km swimming performance or influence RPE in elite swimmers. Although this represents the first analysis in continuum of glycemia in elite endurance swimmers, which suggests that 10km swimming at a racing pace does not lead to hypoglycemia, the need and/or effectiveness of CHO supplementation on endurance performance in open water should be further explored.